Compulsory Tools in Combating Human Trafficking Law Iraqi A Jurisprudential Evaluation Study - Ardawan Mustafa Ismael; Karzan Faqikhalil Kareem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Human trafficking is a serious, deadly and complex crime, which poses an imminent and heinous threat to society and humanity that affects human rights and the humiliation of its dignity, and that it spreads and expands in its new colours as humanity develops and humanity advances, and Iraqi legalization makes efforts to combat trafficking. Human beings, and felt the seriousness of this crime and as a preliminary step Legislation of the combating human trafficking law no. (28) in the year (2012), but it contained a shortage, palaces and gaps in terms of content and drafting where it needs to be corrected In light of Islamic law, positive laws are too late for Islamic law. This study the shortcomings contained in the combating human trafficking law Iraqi No. 28 of 2012 and related to coercive means and their evaluation in the light of Islamic law and put forward appropriate proposals and amendments to fill the shortages, shortcomings and gaps by indicating the legitimate treatment of them, and in conclusion the researchers reached several findings and recommendations.